Cal viva en el fraguado de geopolímeros con piedra pómez de Ecuador. - Chiguano Crespo, Karen Tatiana (2024)
Geopolymers are known to be used as substitutes for Portland cement, due to their low carbon dioxide emissions in their production process, their high thermal and chemical resistance, as well as their good mechanical properties at ambient and extreme temperatures. Research has been carried out in the area of geopolymers and geopolymer concretes, focused on compressive strength, dosage of alkane binder solution, aggregate content, sodium hydroxide concentration, temperature, and duration of curing in ovens, but not on curing at room temperature by incorporating a material that generates endogenous heat in the mixture. The objective of this research is to analyze a curing alternative for geopolymers designed with pumice, which does not require the use of ovens, through the incorporation of quicklime into the mixture and thermal insulation. A mixture of calcium oxide, magnesium oxide, and sodium hydroxide was used as an alkaline activator. The curing of the specimens was carried out without using a swimming pool and at room temperature. The results showed strengths higher than 1.25 MPa and 1.65 MPa at 8 and 9 days of curing, respectively. A geopolymer elaboration methodology was developed that does not require the use of laboratory equipment, which facilitat es its practicality and replication on site.